2002
DOI: 10.1056/nejmoa013202
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptives and the Risk of Breast Cancer

Abstract: Among women from 35 to 64 years of age, current or former oral-contraceptive use was not associated with a significantly increased risk of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
177
2
16

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(223 citation statements)
references
References 15 publications
15
177
2
16
Order By: Relevance
“…Multiple studies using different hormone formulations have reported contradictory effects of estrogen͞progestin use in breast cancer risk (9) and coronary heart disease (10). In light of our findings, discrepancies in outcomes could be, in part, attributable to differences in the cellular responses induced by different progestins.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Multiple studies using different hormone formulations have reported contradictory effects of estrogen͞progestin use in breast cancer risk (9) and coronary heart disease (10). In light of our findings, discrepancies in outcomes could be, in part, attributable to differences in the cellular responses induced by different progestins.…”
Section: Discussionmentioning
confidence: 54%
“…Because progestins are added to HRT to prevent hyperplasia of the endometrium (7) and resulting uterine cancer (8), possible impacts of progestins need to be determined. Numerous studies have found contradictory effects of estrogen͞ progestin use and breast cancer (9), coronary heart disease (10), and cognition (11,12). Although some of these studies used the same hormone formulation [conjugated estrogens (Premarin) with medroxyprogesterone acetate (MPA; Provera)], many did not determine or subdivide the type of progestin used (9)(10)(11)(12)(13)(14), raising the possibility that the apparent discrepancies in outcomes are due to the differences in cellular responses induced by different progestins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the original intention of studying lung injury in this cohort, data on some variables (e.g., age at menarche, hormone replacement therapy, and parity) was not obtained (50,51). These women received high-dose chemotherapy and BCT for high-risk disease and are therefore not representative of all women at risk for breast cancer (52).…”
Section: Discussionmentioning
confidence: 99%
“…Гормональний дисбаланс у тканинах МЗ в бік дефіциту прогестерону супроводжуєть-ся набряком і гіпертрофією сполучної тканини, а проліфе-рація епітелію протоків призводить до утворення кіст [7]. В генезі розвитку патології МЗ серед гормонів передньої долі гіпофізу особливе місце займає пролактин [23]. КЛАСИФІКАЦІЯ Є велика кількість класифікацій мастопатій.…”
Section: етіопатогенезunclassified